Two new species of the genus Aporcelinus Andrássy, 2009 (Nematoda, Dorylaimida, Aporcelaimidae) from Vietnam - Nguyen, Thi Anh Duong; Abolafia, Joaquín; Bonkowski, Michael; Peña-Santiago, Reyes (Zootaxa, 2016)
Two new species of Aporcelinus from Vietnamese natural habitats are studied, described and illustrated, including line drawings and light microscope (LM) pictures. Aporcelinus paramamillatus sp. n. is characterized by its 1.71–2.14 mm long body, lip region 21–22 μm broad, odontostyle 22–24 μm long at its ventral side, neck 451–503 μm long, uterus tripartite and 71–94 µm long, V = 53–54, tail conical with finely rounded tip, ending in a short peg-like terminus, occasionally slightly re-curved dorsad (24–34 μm, c = 50–77, c’ = 0.6–0.9) and unknown male. Aporcelinus paraseychellensis sp. n. is distinguished by its 1.20–1.46 mm long body, lip region 16–18 μm broad, odontostyle 20 μm long at its ventral side, neck 354–368 μm long, uterus tripartite and 176–241 µm long, V = 52–54, tail conical with acute tip and hardly re-curved dorsad, spicules 62 μm long, and 12 regularly spaced ventromedian supplements lacking hiatus.